Kajian Penggunaan Obat Antituberkulosis Pada Pasien Tuberkulosis Paru Dewasa Di Rumah Sakit Umum Daerah Pandan Arang Boyolali Tahun 2016 - Rahmawati, Yulia; , Dra. Nurul Mutmainah, M.Si., Apt (2017)
Tuberculosis is the world's largest health problem since 1995. To reduce the rates of illness and death in TB patients the success of therapy is preferred. One of the factor that influence the success of therapy is the rational therapy and appropriate treatment (appropriate dosage), patient compliance in taking the drug, supervision when taking the drug, adequate services from health foundations, and patient education level. This study aims to determine the description of antituberkulosis treatment and know the accuracy (exact patient, exact drug and proper dose) use of OAT in patients with adult pulmonary tuberculosis at Pandan Arang Boyolali General Hospital in 2016. This research includes a descriptive type of research conducted retrospectively by taking data from medical records. Processing of research results done after obtaining medical records that meet the inclusion criteria that include: 1. Patients diagnosed with adult pulmonary TB. 2. Patients who undergo inpatient or outpatient at RSUD Pandan Arang Boyolali. 3. Patients with complete treatment data (diagnosis, weight, type of patient (TB category), disease history, drug name, dosage regimen, and frequency of drug administration). 4. Patients who are at least 2 months of treatment and then analyzed by reference to the National Guidelines for Tuberculosis Control 2014. Result of research from 35 TB patients at Pandan Arang Boyolali General Hospital in 2016 there were 32 patients using OAT FDC (91,43%) and OAT Kombipak as many as 3 patients (8,57%). The results of the study on the accuracy of the use of drugs obtained as many as 100% right drugs, 100% right patients, and 48.57% right dose